Finite element analysis of surface indentation on turbo-drill thrust ball bearing. Issue 3 (1st September 2020) - Gou, Ruyi; Zhang, Xiaodong; Yang, Wenwu; Chang, Xueping
ABSTRACT: In harsh drilling conditions (e.g. abrasive drilling fluid), turbo-drill thrust ball may suffer from raceway surface indentation under the high axial load. The indentation can cause early failure of the bearing components. This paper establishes a micro-scale finite element model (FEM) to discuss the raceway surface indentation resulted from solid particle. For the sake of simplicity, the interaction between steel ball and solid particle as the latter is pressed into the raceway surface was depicted by axial and circumferential displacements. The distribution of stress and strain in solid particle and raceway surface was obtained from the finite element analysis. Through the discussion on solid particle ellipticity and the effect of friction coefficient on indentation features, it is learned that the variation in ellipticity has a slight impact on indentation depth, but a marked effect on raceway surface deformation; the friction coefficient has a significant impact on indentation edge shape and bottom centre of indentation. The simulation results provide a valuable reference for prevention of bearing raceway indentation.